Formation and stabilization of multiple water-in-water-in-water (W/W/W) emulsions. (May 2020) - Beldengrün, Y.; Dallaris, V.; Jaén, C.; Protat, R.; Miras, J.; Calvo, M.; García-Celma, M.J.; Esquena, J.
Abstract: Multiple Water-in-Water-in-Water (W/W/W) emulsions were prepared, stabilized and characterized. The main objective was to find a simple and low-cost method for the preparation of W/W/W emulsions. The system composed of gelatin, maltodextrin and water was used, and two different methods were studied for producing multiple emulsions in this system. In the first method, maltodextrin-in-gelatin (M/G) emulsions with small droplet size were formed by pH-induced nucleation of maltodextrin droplets, and afterwards, maltodextrin-in-gelatin-in-maltodextrin (M/G/M) multiple emulsions were obtained by dispersing M/G droplets into maltodextrin solutions. The second method consisted in cooling down gelatin-in-maltodextrin (G/M) emulsions, leading to the spontaneous formation of inner maltodextrin droplets. The latter method allowed producing more homogenous M/G/M multiple emulsion droplets. The colloidal stability of such emulsions greatly improved with the addition of mucin particles, which is a glycoprotein that adsorbs on the G/M interface. Stable M/G/M multiple emulsions have been prepared and characterized by fluorescence optical microscopy, where contrast has been enhanced through covalently labelling the various components with fluorescent dyes. To our knowledge, this is the first report of a simple and cost-effective method for the production of multiple W/W/W emulsions, without using microfluidic techniques. Moreover, the present work also demonstrates that mucin microparticles can be effective stabilizers for protein-in-polysaccharide emulsions, and these dispersions can be easily prepared by phase transition methods. Graphical abstract: Image 1 Highlights: Multiple Water-in-Water-in-Water (W/W/W) emulsions have been obtained in gelatin-maltodextrin aqueous mixtures. These emulsions have been obtained by phase transitions, induced by changing pH or temperature. Multiple W/W/W emulsions have been prepared by a simple and cost-effective method, without using microfluidic devices. Multiple W/W/W emulsions have been stabilized with mucin microparticles.